Correlation Between Health Worker's Support and Coping Strategy to Mother's Resilience Level in Managing Annual Flood in the COVID-19 Pandemic - Setiya Dewi, Yulis; Qona'ah, Arina; Alfaruq, Fikri (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Low coping strategies and health worker factors reduce the ability to survive from flood. This can lead to low mother’s resilience. This study aims to analyze the correlation between health worker factors and coping strategy against mother’s resilience in managing the impact of annual flood disasters during the COVID-19 pandemic. This research used correlational analytic method with cross sectional approach. This study used a sample of 121 mothers in Sukorejo Village, Karangbinangun District, Lamongan Regency who were affected by flood. The research instrument used a questionnaire of support, facilities, and motivation health workers;copingstrategy; and mother’s resilience. Spearman Rho Analysis correlation test was used as analytic approach with a significance of <0.05. The data obtained analyzed using a Spearman Rho correlation test. There was a correlation between health worker factors and mother’s resilience (p=0.003: r=0.264). In addition, there was a correlation between coping strategies and mother’s resilience (p=0.000: r=0.369). The higher health workers factor and mother’s coping strategies level, the higher mother’s resilience managing the flood impact. Capacity building for health workers is needed to be able to educate mothers about flood impact management, so that ultimately improve their coping strategies.